Effects of five weeks of prescribed and self-paced high-intensity interval exercise on perceptual responses and health markers in overweight-to-obese adults - Ayob, Nur Anis Lyana (2023)
Background: Previous studies have shown that when overweight/obese adults are permitted to self-pace their exercise intensity during a continuous exercise protocol, it tends to generate greater positive affective response (more pleasurable) compared to the prescribed based exercise, but these have yet to be explored in the context of high-intensity interval exercise (HIIE) in overweight-to-obese adults. Thus, the purpose of this thesis is to examine the effect of 5 weeks of self-paced HIIE (SHIIE) and prescribed HIIE (P-HIIE) on health parameters and perceptual responses among overweight-to-obese adults. Method: Twenty overweight-to-obese adults (mean ± SD; aged 26.7 ± 4.9 years old; BMI = 27.5 ± 4.2) were randomly assigned to two groups, namely, P-HIIE and S-HIIE. Both protocols consisted of 7 to 9 repetitions of 1 minute work intervals performed at either 90% of maximal aerobic speed (P-HIIE) or self-paced running (S-HIIE) separated by 75 s of recovery interval across a 5-week intervention (triweekly, 15 sessions). Health parameters (blood glucose, total cholesterol, triglyceride, HDL, LDL, total cholesterol HDL, and non- HDL) were collected before and after intervention. Whereas perceptual responses (affective, perceived exertion, and enjoyment) were measured before, during, and after each HIIE session (sessions 1, 8, and 15) in both groups. Result: P-HIIE group elicited greater running speed compared to S-HIIE group at work-interval 1 and workinterval 4 in session 1 (all P<0.03, all effect size (ES)>0.98). Also, a greater running speed was evident in P-HIIE compared to S-HIIE at work interval 1 during session 8 (P<0.05; ES= 0.92). P-HIIE group elicited lower affective responses measured via feeling scale (FS) at work interval 1, 4 and end work intervals compared to S-HIIE in session 1 (all P< 0.03, all ES> 0.66). Also, P-HIIE group also elicited lower FS at the end of work interval during session 1 than sessions 8 and 15 (P<0.05; ES>0.78). Both groups generated comparable post-enjoyment pattern across all exercise sessions (all P<0.02, all ES>0.74). P-HIIE group produced greater RPE across all work intervals in session 1 compared to session 8 and 15 (all P< 0.01, all ES>2.13). Both groups enhanced V ̇O2max (ES>0.71) and running speed (ES=0.95 and 1.05, respectively), but no significant difference was observed in all blood markers for both groups. Conclusion: Findings show that S-HIIE and P-HIIE protocols produce a comparable effect of perceptual responses and health indicator (i.e., V ̇O2max) over a 5-week exercise intervention in the overweight and obese cohort.